THE SEROPOSITIVITY OF PARVOVIRUS B19 AMONG KIDNEY TRANSPLANT RECIPIENTS (Iraqi Journal of Medical Sciences, 2017)
Background: Parvovirus B19 (PV-B19) is a single strand DNA virus that is responsible for causing several diseases in humans. Parvovirus B19 induced persistent anemia or/and pancytopenia or/and reticulocyteopenia in renal transplant recipients (RTRs).Objective: To find out any association between PV-B19 reactivation / primary infections with abnormal renal function tests, and post-transplantation period in renal transplant patients.Methods: A quality enzyme linked immunosorbent assay technique was applied for detection of anti-human PV-B19 IgM (DRG-Germany) and IgG (DRG- Germany) in sera of 50 renal transplant recipients followed up for three successive months and 50 normal were collected from the Center of Kidney Diseases and Transplantation in the Medical City of Baghdad and Al-Khayal Hospital and other many private laboratories, Iraq, during the period from August 2015 till February 2016. The age was ranged from 11-57 years.Results: This prospective study included fifty renal transplant recipients with fifty subjects as a control group. The mean ± standard deviation of ages for RTRs was 32.90 ±12.76, which was comparable to that of healthy controls mean 34.02 ± 14.23 ranging for both RTRs and control group between 11-57 years old. Thirty five (70%) RTR aged less than 40 years, and the remaining fifteen (30%) were above 40 years old, and 38/50 (76%) of these RTRs were males. Seropositivity rate in control was 2/50 (4%) but seropositivity rate in patients was 10% (5 cases) and 10% (5 cases) as turning positive for an individual occurrence of human PV-B19 IgM alone at P value = 0.0299 and 9/50 (18%) from control positive for IgG, while 60% (30 cases) for a similar individual rate of positive human parvovirus B19 IgG at P value < 0.0001.Conclusion: The human PV-B19 infection rate was significantly higher among renal transplant recipients than normal controls. Infections correlated with abnormal renal functions tests, and which may in turn cause anemia and/or reticulocytopenia.Keywords: Parvovirus-B19, anemia, reticulocytopenia, renal transplant recipients, ELISACitation: Zainab A. Hlail, Ahmed S. Abdulamir, Ali J.H. Al-Saedi. The seropositivity of Parvovirus B19 among kidney transplant recipients. Iraqi JMS. 2017; Vol. 15(1): 88-93. doi: 10.22578/IJMS.15.1.11